Malice House / a novel - Shepherd, Megan (Los Angeles : Hyperion Avenue, 2022)
Deciding to illustrate a disturbing, secret handwritten manuscript from her late Pulitzer Prize-winning father, aspiring artist Haven Marbury is plunged into a nightmarish world when a monstrous creature appears, forcing her to uncover dark, otherworldly family secrets to rewrite everything she thought she knew about herself.
Clearing out her fathers seaside house, artist Haven Marbury finds a handwritten manuscript: Bedtime Stories for Monsters. Its interweaving short stories crawl with horrific monsters and enigmatic humans that exist somewhere between this world and the next. The stories entice Haven to illustrate them while she stays in the house that her father warned her was haunted. Reeling from a failed marriage, Haven hopes an illustrated Bedtime Stories can be the lucrative posthumous father daughter collaboration she desperately needs to jumpstart her art career. Someone keeps trying to break into her house, and then a monstrous creature appears under Havens bed right as grisly deaths are reported in the nearby woods. She must race to uncover dark, otherworldly family secrets, completely rewriting everything she ever knew about herself in the process.
Keywords: Women artists -- Fiction; Family secrets -- Fiction; Manuscripts -- Fiction; Monsters -- Fiction; Paranormal fiction; Paranormal fiction; Horror fiction; Paranormal fiction; Novels